YOLOv3 and YOLOv5-based automated facial mask detection and recognition systems to prevent COVID-19 outbreaks - Md Asifuzzaman Jishan; Ananna Islam Bedushe; Md Ataullah Khan Rifat; Bijan Paul; Khan Raqib Mahmud (Association for Scientific Computing Electronics and Engineering (ASCEE), 2023)
Object detection system in light of deep learning have been monstrously effective in complex item identification task images and have shown likely in an extensive variety of genuine applications counting the Coronavirus pandemic. Ensuring and enforcing the proper use of face masks is one of the main obstacles in containing and reducing the spread of the infection among the population. This paper aims to find out how the urban population of a megacity uses facial masks correctly. Using YOLOv3 and YOLOv5, we trained and validated a brand-new dataset to identify images as